Evaluating the Impact of Liquidity and Solvency on Profitability: An Empirical Study - Neogy, Taposh Kumar; Hossain, Md. Solaiman; Rahman, Md. Obaidur (Global Disclosure of Economics and Business, 2023)
The study aims to assess how solvency and liquidity affect profitability. Five conventional PCBs were used as a sample in the investigation using the judgmental sampling technique. This study is considered a five-year study period spanning from 2015 to 2019. Annual reports of sample banks and other pertinent sources have been consulted in collecting and utilizing secondary data. The study used multiple regression analysis to examine how various liquidity and solvency indicators affect profitability characteristics. The findings indicate that cash ratio, CAR, DER, and DAR do not significantly affect ROA, whereas CR and WCR do. Conversely, although CR, CAR, and DER significantly impact EPS, cash ratio, WCR, and DAR have no considerable effect on EPS.